A percepção de alunos do ensino médio sobre os direitos humanos - Mazari, Elenilson José (2019)
Understanding respect for human rights as a fundamental practice for living in society and still considering the school as an environment in which these values can be intensified, this research focuses on high school students and their perceptions about such rights. The objective was to capture these visions by applying dynamics in the classroom where students positioned themselves as debaters and, therefore, built arguments in relation to the situations in which they were placed based on news of recent situations in which human rights were violated. The collection took place in a third year high school class of a private school in the interior of São Paulo and the data were collected from the organization of operative groups that, besides the research methodology, showed interesting strategies as teaching methodology. Five dynamics were used to allow students to reflect on different topics such as labor rights, ethics, religious intolerance, transphobia, criminal majority and torture. The data were analyzed from the conception of Human Rights based on recent studies, official documents and the concepts developed by philosopher Hannah Arendt, especially labor, action and public space. The students demonstrated that the misrepresented views on human rights were more linked to their common sense than to their stance on the debated cases, generally positioning themselves alongside the articles declared by the UN in 1948. In this sense, We realize the importance of creating a favorable environment for labor to become action, according to Arendt's ideas.